Chemical composition of essential oil from the bark of Croton cajucara Bentham - Silva, Fabiano Rosa (2012)
The essential oil from the bark of Croton cajucara Bentham, popularly known as sacaca or cajuçara, was obtained by hydrodistillation, yielding 1.28% of the former bark mass, and analyzed by gas chromatography (GC) and gas chromatography coupled to mass spectrometry (GC-MS). In total, 50 compounds were identified, with oxygenated sesquiterpenes composing the majority of components. The main compounds identified were: cyperene (12.36%), α-guaiene, (11.50%) and epi-β-Santalene (8.70%)._________________________________________________________________________________________ RESUMO: The essential oil from the bark of Croton cajucaraBentham, popularly known as sacaca or cajuçara, was obtained by hydrodistillation, yielding 1.28% of the former bark mass, and analyzed by gas chromatography (GC) and gas chromatography coupled to mass spectrometry (GC-MS). In total, 50 compounds were identified, with oxygenated sesquiterpenes composing the majority of components. The main compounds identified were: cyperene (12.36%), α-guaiene, (11.50%) and epi-β-Santalene (8.70%).